Study of the Impact of Organic Manures and Biofertilizers on growth of Phaseolus aureus Roxb. - Bhalshakar, Chhaya (Nepal Journal of Biotechnology, 2020)
Weed sare wild plants growing where they are not wanted, and they compete with the cultivated crop for nutrition. Though they are seen as agricultural waste throughout the year, they are rich sources of nutrients. They grow in abundance during the rainy season, but as the season ends these biomasses get wasted. In the present investigation, Tephrosia hamiltonii Drumm belonging to family Fabaceae, and Achyranthes aspera L. belonging to the family Amaranthaceae were used as a nutrient source to develop crop Phaseolus aureus Roxb. Weed manures, Vermicompost and Compost, were prepared by using weeds T.hamiltonii Drumm and A.aspera L. in 1:1 proportion. Chemical analysis of weed and weed manures were done before administering it into the soil. Neem cake was also used as one of the organic manures. In the experiment, a single dose of biofertilizers Azotobacter and Phosphate solubilizing bacteria were mixed with Weed Vermicompost, Weed Compost and Neem cake; and in one of the treatments, only biofertilizers were used indouble dose. Treatments were given to the crop as ATVB, ATCB, NCB, BioD, NPK, and Control in a randomized block design of experimental plot size 1.5X 1.5 m. The use of chemical pesticides or fertilizers was completely avoided except for NPK treatment plots. Single plant analysis of pulse crop P. aureus Roxb. was done. Observations were recorded in the forms of fresh weight and dry weight of root, stem, leaves, leaf (4th number), and legumes. Total fresh yield (kg ha-1), DM (kg ha-1) increase over control, and Nitrogen efficiency ratio were recorded. Results showed that %DM (an increase over control) and DM kg ha-1 recorded highest in ATVB treatment and the highest N efficiency ratio was in BioD. The present investigation emphasized reducing the input cost of the farm products along with protection of the environment and natural resources.